Comparison of the Bentall procedure versus valve-sparing aortic root replacement. Issue 4 (1st October 2020) - Hamandi, Mohanad; Nwafor, C. Ikenna; Baxter, Ronald; Shinn, Kathryn; Wooley, Jordan; Vasudevan, Anupama; Harrington, Katherine; Schaffer, Justin; Moore, David; DiMaio, J. Michael; Ryan, William H.; Brinkman, William T.
Abstract: Bentall and valve-sparing root replacement (VSRR) procedures are established treatments for aortic root disease. We present a single-center retrospective analysis comparing outcomes of bioprosthetic Bentall (BB), mechanical Bentall (MB), and VSRR patients from November 2007 to October 2016. Survival analysis was performed to evaluate the composite endpoint of freedom from recurrent aortic insufficiency, reoperation, or death. Of the 170 patients, BB was performed in 36 patients, MB in 63 patients, and VSRR in 71 patients. For BB, MB, and VSRR, the mean age was 63.8, 45.5, and 49.2 years ( P  < 0.001), respectively. Additionally, significantly more patients in the MB group (n = 32, 50.8%, P  < 0.001) than in the BB and VSRR groups had prior cardiac surgeries. Cardiopulmonary bypass time and cross-clamp time were significantly longer in the VSRR group ( P = 0.04 and 0.0005, respectively). Despite the complexity of the procedure, VSRR patients had higher combined freedom from death and reoperation than patients in the BB or MB groups. Elective Bentall root replacement is an excellent option for patients with root disease. Patients undergoing Bentall tend to have more severe or emergent cases, making them unlikely candidates for VSRR. VSRR in experienced centers carries equivalent morbidity and mortality and improved survival.